Seasonal Variation in Leaf Physiology and its Relationship with Nitrogen Dynamics in Albizia amara Boivin - Shanker, Arun K; Bisaria, A K; Handa, A K; Solanki, K R (Annals of Arid Zone, 2016)
A study on seasonal variation in leaf physiological parameters and dynamics of nitrogen metabolism was conducted in Albizia amara, a fodder-yielding, droughtresistant and fire-hardy tree of the arid and semi-arid regions of India, in National Research Centre for Agroforestry, Jhansi. Rate of transpiration and resistance to diffusion by stomata of the leaves of Albizia amara were inversely related and showed significant seasonal variation. Higher leaf temperatures were observed in summer season (March to June). Relative water content during winter months (November to February) and monsoon (July to October) were significantly higher than that in the summer. High leaf transpiration rates reduced relative water content signiticantly. Total nitrogen did not exhibit a distinct linear relationship with nitrate reductase activity, although they were directly related. Signiticant variations in nitrate reductase activity due to season were observed. Nitrate reductase activity showed distinct relationships with diffusive resistance, transpiration rate and relative water content. Summer season showed significant difference in all the parameters recorded in comparison with that in winter and monsoon.